2007
DOI: 10.1152/ajprenal.00495.2006
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of the VEGF-endothelial nitric oxide axis in diabetic nephropathy: an explanation for the paradoxical effects of VEGF in renal disease

Abstract: In many forms of experimental kidney diseases, renal VEGF is low, and administering VEGF can be shown to be protective. A paradox occurs in diabetes, in which renal VEGF levels are high and a deleterious effect of VEGF on kidney disease has been shown. We have hypothesized that endothelial dysfunction induced by hyperglycemia or other factors may underlie the pathogenic mechanisms of a high VEGF state. VEGF normally stimulates endothelial nitric oxide (NO) release and acts in concert with elevated NO levels as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
91
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 78 publications
5
91
0
2
Order By: Relevance
“…20 Thus, negative regulation of VEGFRs by NO could be a key mechanism to maintain vascular integrity and macrophage migration under VEGF stimulation. 18 Our findings that NO negatively regulated the cell spreading response in macrophages in response to VEGF are also compatible with previous studies that have shown that NO could inhibit actin polymerization in response to VEGF on neutrophils. 36 In summary, VEGF activates macrophage migration by Flt-1.…”
Section: Cd68 M∅ In Glomerulisupporting
confidence: 93%
See 1 more Smart Citation
“…20 Thus, negative regulation of VEGFRs by NO could be a key mechanism to maintain vascular integrity and macrophage migration under VEGF stimulation. 18 Our findings that NO negatively regulated the cell spreading response in macrophages in response to VEGF are also compatible with previous studies that have shown that NO could inhibit actin polymerization in response to VEGF on neutrophils. 36 In summary, VEGF activates macrophage migration by Flt-1.…”
Section: Cd68 M∅ In Glomerulisupporting
confidence: 93%
“…We have recently reported that diabetic endothelial nitric oxide synthase (eNOS)-deficient mice develop advanced diabetic nephropathy, characterized by mesangial expansion, basement membrane thickening, mesangiolysis, glomerular microaneurysms and Kimmelstiel-Wilson-like nodules, all of which characterize human diabetic nephropathy. 17 Interestingly, these advanced lesions were accompanied with an increase in renal VEGF expression, suggesting that uncoupling of VEGF with endothelial NO could provoke severe glomerular lesions (reviewed in Nakagawa 18 ). Here, we examined the association of macrophage infiltration with VEGF in glomerular lesions of diabetic eNOS-deficient mice.…”
mentioning
confidence: 99%
“…34 Part of this effect is probably due to the attenuation of VEGF-A signaling, which contributes to vascular stability by limiting blood vessel proliferation. In addition, Angpt1 increases eNOS Ser 1177 phosphorylation, resulting in sustained nitric oxide levels, 35 which preserves the integrity of interendothelial junctions in capillaries and inhibits angiogenesis and vascular permeability, 36,37 in physiologic nondiabetic conditions. 38 In our study, we demonstrated that eNOS Ser 1177 phosphorylation was markedly increased in diabetic mice when Angpt1 levels were restored.…”
Section: Discussionmentioning
confidence: 99%
“…Известно, что VEGF стимулирует высвобождение NO как трофического фак-тора для эндотелия, при этом сам является сильным ми-тогеном для эндотелиоцитов. Эта реакция регулируется по принципу обратной связи [21]: повышенный уровень NO подавляет активность VEGF. Со временем при диа-бете этот процесс нарушается, происходит разобщение оси «NO-VEGF», и несдерживаемый высокий уровень фактора роста эндотелия сосудов приводит к развитию и прогрессированию осложнений [22].…”
Section: Discussionunclassified